Uma análise dos impactos socioeconômicos e ambientais do Rodoanel Mário Covas em São Paulo numa visão sobre a evolução do planejamento em infraestrutura de transportes - Fabiano, Maria Lucia Alves (2014)
The purpose of this work is to study the ring Beltway, analyzing the project as a tool for sustainable development in the RMSP, identifying its limits and contradictions and its importance and magnitude as investment in road transport, at a time when the country is facing bottlenecks in infrastructure, as well as proximity to a major event in the city that is the World Cup in 2014. In this context, the discussion comes to light on the serious problem of transport infrastructure in the region and in Brazil, the concern of immobility in large urban centers, plus the need for a more effective and sustainable urban planning. In addition, the Rodoanel, appears as a road project, full of controversial issues, the socioeconomic and environmental context, requiring large amount of financial resources, in addition to conflicts of interest and uncertainty about the real benefits of the project